Default Premiums in Commodity Markets: Theory and Evidence - BAILEY, WARREN; NG, EDWARD (Journal of Finance, 1991)
ABSTRACT We model the effect of nonperformance risk on forward and futures pricing and look for evidence of nonperformance risk in precious metals futures prices from the “Hunt Brothers”episode. Changes in default premiums are measured and related to the sequence of events in the metals markets during this period. Results suggest first that ex ante costs of nonperformance can be a significant, priced factor in commodity markets and second that the arrival of new information is often associated with changes in these costs. The evidence has implications for both theoretical and empirical research on commodity markets.